(untitled) (Praxis Educativa, 2016)
Nowadays there is an increasing interest in the use of different tools, such as Scratch, to teach and learn programming in educational contexts. The present article inquires about Scratch developers´ discourses and their guidance for teaching and learning programming, aiming to promote Mediated Educational Practices that make possible the co-construction of technologies for social inclusion in formal and non-formal contexts. Sociotechnical approach and the methodological framework of Dynamic Hypermedia Device are the theoretical bases of this exploratory and qualitative study. From results´ analysis it can be concluded that barriers for co-constructions of technologies for social inclusion in educational contexts are not related to limitations of the tool itself, but to the instrumental orientation of the educational practices.